1997
DOI: 10.1007/s004210050269
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between isocapnic buffering and maximal aerobic capacity in athletes

Abstract: This study was performed to clarify the relationship between isocapnic buffering and maximal aerobic capacity (VO2max) in athletes. A group of 15 trained athletes aged 21.1 (SD 2.6) years was studied. Incremental treadmill exercise was performed using a modified version of Bruce's protocol for determination of the anaerobic threshold (AT) and the respiratory compensation point (RC). Ventilatory and gas exchange responses were measured with an aeromonitor and expressed per unit of body mass. Heart rate and rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…In this study, the ICB phase was higher in team sport athletes than endurance athletes despite the VO2max being higher in the endurance athletes. Oshima et al showed that the ICB phase is more strongly correlated with the VO2max than the AT in athletes (7). However, the sample size was too small for regression analysis in these studies.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…In this study, the ICB phase was higher in team sport athletes than endurance athletes despite the VO2max being higher in the endurance athletes. Oshima et al showed that the ICB phase is more strongly correlated with the VO2max than the AT in athletes (7). However, the sample size was too small for regression analysis in these studies.…”
Section: Discussionmentioning
confidence: 82%
“…Previous studies indicated a positive correlation between the ICB phase and VO2max in athletes (7,23). On the other hand, according to some researchers, the ICB phase is not related to the endurance performance in endurance athletes (11).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations